Use of Biophysical Methods in Animal Husbandry (The Peerian Journal, 2022)
Early assessment of the functional status of the organism of farm animals, the development of appropriate, reliable, highly sensitive methods to predict their future breeding and productivity remains the most important challenges of our industry